4D printing of PET-G via FDM including tailormade excess third shape. (August 2022) - Soleyman, E.; Aberoumand, M.; Soltanmohammadi, K.; Rahmatabadi, D.; Ghasemi, I.; Baniassadi, M.; Abrinia, K.; Baghani, M.
Highlights: Assessment of PET-G 4D printing as a controversial SMP including different printing parameters. Obtaining and controlling of the excess curved third shape as the new permanent shape via printing parameters. Showing superior shape memory behavior of PET-G 4D printed part regardless of printing condition. Abstract: In this paper, for the first time, the 4D printing capability and shape memory effect of PETG as a novel shape memory thermoplastic has been investigated with an option of emerging tailormade excess curved third shape during the shape recovery step. A self-bending through the primary printed layers was observed due to entropic force relief caused by functionally-graded polymer chain extension in each layer. Implementation of printing temperature and speed of 200 ◦ C and 70 mm/s, respectively, results in an opaque appearance and a more curved third shape. On the other hand, a transparent appearance with a gentle curved permanent shape was achieved by the parameters of 240 ◦ C and 10 mm/s. The observations are attributed to the effect of printing parameters on the degree of polymer chains' extension and its difference for each layer. Both samples show an exemplary shape memory effect behavior with higher than 96 % total shape recovery.